Peran Media Utama Citaku Terhadap Kertampilan Berfikir Peserta Didik Kelas IV SD - Irgi Ahmad Fahrozi; Nur Khoiri; Iin Purnamasari (JANACITTA, 2020)
Education using the 2013 curriculum must be able to improve students' skills and values that apply in society. Critical thinking skills, among others, that must be possessed by students to support students' thinking and self-development. For this reason the need for innovation and good creativity from the teacher so that students get the goals that have been designed in learning. In learning, teachers usually still use conventional learning systems and are not added to the media. These impacts cause students to be unenthusiastic, enthusiastic about learning and even result in actual skills emerge and will increase students' potential to sink. Therefore teachers must design and create media to improve students' critical thinking skills. These media UTAMA CITAKU media which have a role in improving students' critical thinking skills.